Solid catalyst for treating residual antibiotics or pesticides in drinking water as well as preparation method and application of solid catalyst
By growing Fe-MOF in situ on iron foam and loading CuCe-LDH, CuO-CeO2/Fe2O3/FF catalyst was prepared, which solved the problems of poor reuse performance and difficulty in recycling of existing catalysts, and achieved efficient and stable tetracycline removal effect and simple catalyst recovery.
Patent Information
- Application Number
- CN202411988323.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The catalytic activity of existing heterogeneous electrofenton catalysts has significantly decreased during reuse, and the recovery and regeneration are difficult, which has affected its large-scale application in drinking water treatment.
By growing Fe-MOF in situ on iron foam (FF), a stable Fe-MOF/FF structure is formed, providing a more stable substrate for loaded CuCe-LDH. Combined with optimized hydrothermal and calcining conditions, CuO-CeO2/Fe2O3/FF heterogeneous electrofenton catalyst was prepared.
The catalytic activity and stability of the catalyst are significantly improved, and the recovery and regeneration process is simplified. The removal rate of tetracycline in the catalyst is still 86% after 8 cycles, reducing the operating cost and material waste in actual applications.
Smart Images

Figure CN119771424A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drinking water treatment, and in particular to a solid catalyst for treating residual antibiotics or pesticides in drinking water, a preparation method and use thereof. Background Art
[0002] In recent years, with the widespread use of antibiotics in the fields of medicine, animal husbandry, agricultural planting and food industry, the problem of antibiotic residues has gradually become one of the environmental issues of global concern. Tetracycline is a widely used antibiotic that is widely used because of its high efficiency, low cost and easy access. The large-scale use of tetracycline poses a serious threat to aquatic ecosystems and drinking water safety. Traditional water treatment technology is difficult to effectively remove new pollutants such as tetracycline in water. Therefore, in order to ensure a safe drinking water supply, it is necessary to develop drinking water treatment technology that can efficiently remove these new pollutants.
[0003] At present, the methods for removing tetracycline from drinking water mainly include biodegradation, general chemical oxidation, adsorption and membrane filtration. Although these methods can reduce the concentration of tetracycline in water to a certain extent, they have problems such as low removal efficiency of target objects, high treatment cost, and complex operation and management to varying degrees. For example, the biodegradation method is limited by the activity of microorganisms, has a poor removal effect on new pollutants, and may promote the production of resistance genes; the mineralization rate of the general chemical oxidation method is low and harmful byproducts will be produced; the adsorption method requires frequent replacement of adsorption materials or regeneration of them, which is complicated and relatively costly; membrane filtration requires regular chemical cleaning and physical regeneration of the membrane, which is complicated to operate, increases the consumption of chemicals, and produces concentrated water that is difficult to treat. Therefore, finding an efficient, economical and environmentally friendly method to remove new pollutants (such as residual tetracycline) from drinking water has become one of the research focuses in this field.
[0004] To solve the problem of antibiotic contamination in drinking water, heterogeneous electro-Fenton technology, as a highly efficient advanced oxidation technology, shows great application potential. This technology generates highly oxidizing hydroxyl radicals ( · OH), which can effectively oxidize and degrade new pollutants such as antibiotics in water. Compared with traditional treatment methods, heterogeneous electro-Fenton technology has the advantages of simple operation, high oxidation efficiency, and low secondary pollution. Therefore, developing and optimizing heterogeneous electro-Fenton catalysts and improving their stability and reusability will be one of the main technical paths to solve the problem of antibiotic pollution in drinking water.
[0005] In recent years, many researchers have studied many new heterogeneous electro-Fenton catalysts for removing organic pollutants from water and have achieved good removal effects. However, there are still many problems with existing catalysts, including: poor catalyst reuse performance, and the catalytic activity significantly decreases after multiple cycles; unstable catalytic effect, which is easily affected by the composition, structure and reaction conditions of the catalyst; difficult recovery and regeneration, and traditional methods are difficult to efficiently separate and recover catalysts, and the regeneration process is complex and costly. These problems have severely limited the large-scale application of heterogeneous electro-Fenton technology in the field of drinking water treatment.
[0006] CN117654635A discloses an iron-zinc bimetallic organic framework electro-Fenton catalyst, wherein sodium acetate trihydrate, iron nitrate nonahydrate and zinc nitrate hexahydrate are dissolved in deionized water, stirred at room temperature, centrifuged, washed and dried to obtain Fe / Zn bimetallic clusters. The Fe / Zn bimetallic clusters are dispersed in an organic solvent, a PTA solution is added for stirring, and a 2-methylimidazole solution is added for stirring for reaction, centrifuged, washed and dried to obtain an iron-zinc bimetallic organic framework electro-Fenton catalyst. The catalyst is dispersed in a sodium sulfate electrolyte containing organic pollutants (a mixture of one or more of methylene blue, ciprofloxacin, tetracycline and phenol), connected to a cathode and an aeration device to construct a reaction system to remove target pollutants. However, the iron-zinc bimetallic organic framework electro-Fenton catalyst prepared by this scheme is in powder form, which is difficult to recycle after the reaction. If it is not handled properly, the material will remain in the treated water, which will not only affect the water quality of the effluent, but also cause material waste. The recycled material needs to be chemically cleaned or treated at high temperature before it can be reused, which increases the cost of material reuse. In addition, during the reaction process, the large number of bubbles generated by the aeration device will affect the suspended state of the catalyst, interfere with the catalytic performance of the catalyst, and even break the iron-zinc bimetallic organic framework structure, which will affect the stability of the catalyst.
[0007] CN114618554A discloses a porous iron-nitrogen doped carbon composite electro-Fenton catalytic material derived from iron porphyrin, wherein iron porphyrin, metal oxide (at least one of magnesium oxide, zinc oxide, and copper oxide), and carbonate (at least one of potassium carbonate, potassium bicarbonate, sodium carbonate, and sodium bicarbonate) are mixed and calcined, mixed with a hydrochloric acid solution, ultrasonicated, and allowed to stand to obtain a porous iron-nitrogen doped carbon composite electro-Fenton catalytic material, which is used as an electro-Fenton catalyst for degrading organic pollutants (ciprofloxacin) in water or preparing hydrogen peroxide, which can not only achieve effective degradation of organic pollutants, but also significantly increase the yield of hydrogen peroxide. When the porous iron-nitrogen doped carbon composite electro-Fenton catalytic material derived from iron porphyrin is used for electro-Fenton reaction for 90 minutes, the removal rate of ciprofloxacin is as high as 99.5%, achieving efficient removal of ciprofloxacin. However, the catalyst in this scheme will still be affected by the presence of the aeration device in the electro-Fenton process, which will affect its catalytic performance and structural stability. At the same time, some materials will still remain in the treated water after catalyst recovery, causing water pollution and catalyst loss. In addition, the scheme mentioned that the prepared catalyst can still achieve a removal efficiency of 76% after four cycles. Although it is significantly improved compared with the traditional catalyst scheme, the catalytic performance is still much lower, and the recycling performance of the material is poor.
[0008] Therefore, it is of great practical significance to develop a heterogeneous electro-Fenton catalyst with high catalytic efficiency, easy recovery and high reusability, and use it to remove antibiotic or pesticide pollution in drinking water. Summary of the invention
[0009] In order to overcome the high reagent consumption and poor pH applicability in the traditional electro-Fenton process, · The present invention solves the problems of low OH generation, as well as the problems of difficult recovery or reuse of new heterogeneous catalysts, poor catalytic effect, poor reuse performance and insufficient stability. The present invention provides a solid catalyst for treating residual antibiotics or pesticides in drinking water, a preparation method and an application thereof.
[0010] The present invention prepares a CuO-CeO2 / Fe2O3 / FF heterogeneous electro-Fenton catalyst, in-situ grows Fe-MOF on foamed iron (FF) through a hydrothermal reaction, forms a stable Fe-MOF / FF structure, and provides a more stable substrate for loading CuCe-LDH; then, the CuCe-LDH is loaded on the Fe-MOF / FF substrate to form a stable catalyst structure, and the problems of weak loading, easy falling off, poor stability, etc. of layered hydroxide are improved by bridging the Fe-MOF in-situ grown on the FF with the CuCe-LDH, and the catalytic performance of the material is significantly improved by the composite of multiple metals such as Fe, Cu, and Ce; finally, calcination is performed to form a CuO-CeO2 / Fe2O3 / FF heterogeneous electro-Fenton catalyst with high specific surface area, high catalytic activity, simple recycling and regeneration, and extremely high reusability. Experiments have shown that the recovered catalyst can be reused after a simple deionized water wash, and the tetracycline removal rate is still as high as 86% after 8 cycles. This invention provides a new catalyst preparation method and idea for heterogeneous electro-Fenton technology.
[0011] Specifically, this application provides the following technical solutions:
[0012] A preparation method of a solid catalyst for treating residual antibiotics or pesticides in drinking water, comprising soaking FF in dilute hydrochloric acid and ultrasonically soaking it, then soaking it in ethanol and ultrasonically soaking it, and then washing it with deionized water to obtain a solid one; dissolving PTA in deionized water to obtain a solution one; transferring the solution one to a reactor, and then placing the solid one in the reactor and heating it for reaction; cooling it to room temperature after the reaction is completed, repeatedly washing the obtained solid, and drying it to obtain a solid two, named Fe-MOF / FF;
[0013] At room temperature, prepare Ce(NO3)3·6H2O and Cu(NO3)2·3H2O solutions, add ammonium fluoride and urea, mix well to obtain solution 2, transfer solution 2 to a reactor, and place solid 2 on the inner wall of the reactor; put the reactor into a drying oven, heat it at a constant temperature, wash the obtained solid, and dry it to obtain solid 3; then place solid 3 in a muffle furnace for calcination to obtain solid 4, which is the CuO-CeO2 / Fe2O3 / FF catalyst.
[0014] Furthermore, the specific preparation method of the solid one is to soak a 2cm×2cm FF in 3mol / L dilute hydrochloric acid for 30 minutes, then soak it in ethanol for 30 minutes, and then rinse it with deionized water to obtain solid one. The specific preparation method of the solution one is to add 2mmol of PTA into 60mL of deionized water and stir it continuously until it is completely dissolved to obtain solution one.
[0015] Furthermore, the specific preparation method of the solid two is to transfer the solution one to a polytetrafluoroethylene-lined reactor with a volume of 100 mL, place the solid one in the reactor, heat to 150°C for 12 hours; when the reaction is completed and cooled to room temperature, repeatedly wash the obtained solid with ethanol and deionized water, and dry it at 80°C to obtain solid two, named Fe-MOF / FF.
[0016] 4mmol Ce(NO3)3·6H2O, 12mmol Cu(NO3)2·3H2O, 20mmol ammonium fluoride and 80mmol urea were added to 20mL deionized water respectively, and after they were mixed and dissolved, the pH was adjusted to a neutral range (7.4-7.5) using a mixed solution of Na2CO3 (0.6mol / L) and NaOH (0.3mol / L), wherein the molar ratio of Cu:Ce in the second solution was 3:1. The total molar number of Cu and Ce in the second solution was controlled at 16mmol (12mmol copper, 4mmol Ce).
[0017] The specific preparation method of the solid three is as follows: firstly, the solution two is transferred to a polytetrafluoroethylene-lined reactor, and then the solid two is placed on the inner wall of the polytetrafluoroethylene-lined reactor; the reactor is placed in a blast drying oven, and heated at a constant temperature of 120° C. for 12 hours, and then the obtained solid is rinsed with ethanol and deionized water, and then dried in an oven at 80° C. to obtain the solid three;
[0018] Among them, the specific preparation method of the solid four is to place the solid three in a muffle furnace and calcine it at 400°C for 1 hour to obtain solid four.
[0019] The solid catalyst prepared by the present invention can be used to treat residual antibiotics and pesticides in drinking water, wherein the antibiotics are ciprofloxacin, tetracycline and sulfasalazine; the pesticides are atrazine and imidacloprid. The solid catalyst is used to treat residual antibiotics in drinking water through a heterogeneous electro-Fenton reaction, and the current density of the electro-Fenton reaction is 9 mA / cm 2 , the aeration volume was 0.6 L / min, and the solution pH was 7.2.
[0020] This solid catalyst not only has a high efficiency in the treatment of tetracycline, but also has a good removal effect on other typical antibiotics (ciprofloxacin, sulfasalazine) and pesticides (atrazine, imidacloprid), which proves that the solid catalyst has good catalytic oxidation removal efficiency for typical drugs and the prepared catalyst has good applicability.
[0021] Compared with the prior art, the solid catalyst for treating residual antibiotics or pesticides in drinking water, the preparation method and the application of the present invention have at least the following beneficial effects:
[0022] (1) The preparation method of the present invention first uses the cleaned FF, adds PTA and deionized water to carry out hydrothermal reaction, so that Fe-MOF with good morphology is generated on the surface of FF, providing a more stable matrix for the loading of copper cerium hydroxide. In addition, in addition to providing better structural support, Fe-MOF / FF can also improve the conductivity of the material through Fe-MOF, which is beneficial to electron transmission and thus improves its catalytic ability.
[0023] (2) The CuO-CeO2 / Fe2O3 / FF electro-Fenton catalyst prepared by the present invention has significant advantages in removing antibiotics from drinking water. By optimizing the composition and structure of the catalyst, not only the catalytic activity and stability of the catalyst are significantly improved, but also the problems existing in the traditional electro-Fenton technology are solved. The catalyst can significantly improve the · The generation efficiency of OH was improved, thus achieving efficient removal of tetracycline. Experimental results showed that under optimal conditions, the catalyst could achieve 100% tetracycline removal rate within 75 minutes, which was significantly better than the existing electro-Fenton catalyst.
[0024] (3) High stability and long life: The catalyst has good stability and corrosion resistance, and can maintain high catalytic activity during long-term operation. Even after multiple cycles, the performance of the catalyst remains stable and efficient. Experimental results show that after eight cycles, the removal rate of tetracycline can still reach 86% or more, significantly reducing the frequency of catalyst replacement and operating costs in actual electro-Fenton process applications.
[0025] (4) Easy recovery and reuse: The CuO-CeO2 / Fe2O3 / FF composite catalyst is in solid form and can be easily separated and recovered from the reaction system. The recovered catalyst can be reused after simple cleaning without complicated chemical treatment or high-temperature regeneration, which simplifies the catalyst regeneration process, reduces its processing cost, and has better application prospects.
[0026] (5) This catalyst is not only suitable for removing tetracycline from water, but can also effectively remove other types of pollutants, such as ciprofloxacin, sulfasalazine, atrazine, imidacloprid, etc. By adjusting and optimizing the reaction conditions (such as current density, aeration volume, pH value, etc.), its removal efficiency for different pollutants can be further improved, thus broadening its application range.
[0027] (6) The composite material prepared by the two-step hydrothermal method of the present invention not only strengthens the basic support function of the foamed iron, but also gives full play to the advantages of the copper-cerium bimetallic oxide, thereby having better catalytic performance and application effect. The preparation method of the catalyst is simple, the raw materials used are low in cost, and it is environmentally friendly during its entire preparation and use process, and no harmful by-products are produced. This makes the catalyst have higher economy and environmental sustainability in practical applications, and provides a new and effective method for ensuring drinking water safety.
[0028] The solid catalyst for treating residual antibiotics or pesticides in drinking water, its preparation method and application of the present invention are further described below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1-Figure 2 This is the SEM image of FF.
[0030] Figure 3-Figure 4 This is the SEM image of Fe-MOF / FF.
[0031] Figure 5-Figure 6 This is the SEM image of CuO-CeO2 / Fe2O3 / FF.
[0032] Figure 7 This is the XRD diagram of CuO-CeO2 / Fe2O3 / FF.
[0033] Figure 8 The efficiency of removing tetracycline from drinking water by CuO-CeO2 / Fe2O3 / FF catalyst in heterogeneous electro-Fenton system under optimal conditions.
[0034] Fig. 9 Effect of metal ratio on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0035] Fig.10 The effect of hydrothermal temperature on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in the removal of tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0036] Fig.11 The effect of hydrothermal time on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0037] Fig.12 To investigate the effect of calcination temperature on the removal efficiency of tetracycline from drinking water over CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system.
[0038] Fig.13The effect of calcination time on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in the removal of tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0039] Fig.14 Effect of current density on the removal efficiency of tetracycline in drinking water over CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system.
[0040] Fig.15 The effect of aeration rate on the removal efficiency of tetracycline in drinking water over CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system.
[0041] Fig.16 The effect of solution pH on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in the removal of tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0042] Fig.17 The effect of electrolyte type on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in the removal of tetracycline in drinking water in a heterogeneous electro-Fenton system.
[0043] Fig.18 The effect of initial tetracycline concentration on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline from drinking water in a heterogeneous electro-Fenton system.
[0044] Fig.19 To investigate the effect of drinking water matrix type on the removal efficiency of tetracycline from drinking water over CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system.
[0045] Fig. 20 The removal efficiency of tetracycline in drinking water when the CuO-CeO2 / Fe2O3 / FF catalyst was reused 8 times in a heterogeneous electro-Fenton system.
[0046] Fig.21 It is the removal efficiency of different types of organic matter by CuO-CeO2 / Fe2O3 / FF catalyst in the heterogeneous electro-Fenton system. DETAILED DESCRIPTION
[0047] A preparation method of a CuO-CeO2 / Fe2O3 / FF catalyst for treating residual antibiotics in drinking water, specifically comprising:
[0048] Soak 2cm×2cm FF in 3mol / L dilute hydrochloric acid for 30 minutes and then soak it in ethanol for 30 minutes, then rinse it with deionized water to obtain solid one. Add 2mmol PTA to 60mL deionized water and stir continuously until it is completely dissolved to obtain solution one. Transfer solution one to a polytetrafluoroethylene-lined reactor with a volume of 100mL, place solid one in the reactor, heat to 150℃ and react for 12h. When the reaction is completed, cool it to room temperature, wash the obtained solid repeatedly with ethanol and deionized water, and then dry it in an oven at 80℃ to obtain solid two. Since the Fe-MOF grown on solid two after the reaction forms a composite material with solid one, solid two is named Fe-MOF / FF.
[0049] At room temperature, the method for preparing solution 2 is as follows: 4 mmol Ce(NO3)3·6H2O, 12 mmol Cu(NO3)2·3H2O, 20 mmol ammonium fluoride and 80 mmol urea are weighed, added into 20 mL deionized water, mixed thoroughly and evenly until completely dissolved, and then the pH is adjusted to the neutral range (7.4-7.5) using a mixed solution of Na2CO3 (0.6 mol / L) and NaOH (0.3 mol / L), and then solution 2 is transferred into a polytetrafluoroethylene-lined reactor, and solid 2 (Fe-MOF / FF) is placed on the inner wall of the polytetrafluoroethylene-lined reactor. The reactor was placed in a forced air drying oven and heated at a constant temperature of 120°C for 12 hours. The obtained solid was then washed with ethanol and deionized water and dried in an oven at 80°C to obtain solid three. Solid three was then placed in a muffle furnace and calcined at 400°C for 1 hour to obtain solid four, named CuO-CeO2 / Fe2O3 / FF catalyst.
[0050] The total molar number of metals (Cu and Ce) in solution 2 is controlled at 16 mmol, wherein the molar ratio of Cu:Ce is 3:1, namely, 12 mmol of copper and 4 mmol of Ce.
[0051] Figure 1-Figure 4 The SEM images of FF and Fe-MOF / FF at 500 times and 10000 times respectively. Figure 1-2 It can be seen that the surface of FF is relatively smooth and flat, and its three-dimensional structure is obvious, with a unique mesh-like macroporous structure. Figure 4 It can be seen that after the first hydrothermal reaction, a uniform Fe-MOF was generated on the FF. Figure 3-Figure 4 The corresponding material is named Fe-MOF / FF.
[0052] Figure 5-Figure 6The SEM images of CuO-CeO2 / Fe2O3 / FF materials at 150 times and 10,000 times. It can be seen from the figure that under the optimal preparation conditions, CuCe-LDH becomes metal (Cu, Ce) oxides after calcination and is evenly attached to the substrate. The aforementioned Fe-MOF / FF also becomes Fe2O3 / FF structure after calcination. This unique structure provides it with a larger specific surface area and more active catalytic sites for catalytic oxidation and degradation of tetracycline in the electro-Fenton system.
[0053] Figure 7 Characterization shows that the characteristic peaks at 28.55°, 47.48°, 56.33°, 59.08°, 79.07° and 88.41° correspond to the (111), (220), (311), (222), (420) and (422) crystal planes of CeO2, respectively. The diffraction peaks at 38.71°, 48.72°, 61.52° and 68.12° correspond to the (111), (20-2), (11-3) and (220) crystal planes of CuO, respectively. The diffraction peaks at 33.15° and 35.61° correspond to the (104) and (110) crystal planes of Fe2O3, respectively, and the diffraction peak at 76.58° corresponds to the (222) crystal plane of FeO. The characterization results show that copper-cerium hydroxide and Fe-MOF generate their corresponding metal oxides after calcination.
[0054] Experimental Example 1
[0055] The prepared CuO-CeO2 / Fe2O3 / FF catalyst was added to the electro-Fenton reaction tank, and the cathode and cathode were inserted, the power supply was connected, and aeration was introduced to form a reaction device, which was placed on a 300r / min magnetic stirrer at room temperature (25°C). Samples were taken at reaction times of 0min, 1min, 2.5min, 5min, 10min, 15min, 30min, 45min, and 75min, and the tetracycline concentration in the water sample was determined using an ultra-high performance liquid chromatography-tandem triple quadrupole mass spectrometer.
[0056] The power supply current density is 9 mA / cm, the solution tank contains 300 mL of 0.05 mol / L Na2SO4 electrolyte and 10 mg / L tetracycline, and the initial solution pH is 7.2.
[0057] Among them, the aeration volume of the aeration device is 0.6L / min.
[0058] Among them, the cathode is preferably a 2cm×5cm graphite felt (GF) cathode modified by carbon black and polytetrafluoroethylene (PTFE), and other cathodes can also be used.
[0059] The anode is a 2cm×5cm titanium-based ruthenium-iridium oxide (DSA) anode, and other anodes may also be used.
[0060] Experimental Example 2
[0061] Different from Experimental Example 1, the Cu:Ce molar ratios in the preparation of the CuO-CeO2 / Fe2O3 / FF catalyst in Experimental Example 2 were 0:1, 1:7, 1:3, 1:1, 3:1, 7:1, and 1:0 (total molar number 16 mmol), and the tetracycline concentration was measured by sampling at 75 minutes of reaction. The remaining steps were the same as those in Experimental Example 1. The effect of the ratio of Cu to Ce in the catalyst on the efficiency of the CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in the electro-Fenton system was determined by experiments.
[0062] Experimental Example 3
[0063] Different from Experimental Example 1, in the process of forming solid 3 from solid 2 when preparing CuO-CeO2 / Fe2O3 / FF catalyst in Experimental Example 3, the reaction temperatures were set to 30°C, 60°C, 90°C, 120°C, 150°C and 180°C respectively, and the concentration of tetracycline was measured by sampling at 75 minutes of reaction, and the rest of the steps were the same as Experimental Example 1. The effect of hydrothermal temperature on the removal efficiency of tetracycline by the prepared CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0064] Experimental Example 4
[0065] Different from Experimental Example 1, in the process of forming solid 3 from solid 2 when preparing CuO-CeO2 / Fe2O3 / FF catalyst in Experimental Example 3, the hydrothermal time was set to 4h, 8h, 12h, 16h and 20h respectively, and the tetracycline concentration was measured by sampling at 75min of reaction, and the rest of the steps were the same as Experimental Example 1. The effect of hydrothermal time on the efficiency of tetracycline removal of the prepared CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0066] Experimental Example 5
[0067] Different from Experimental Example 1, in the process of forming solid 4 from solid 3 during the preparation of CuO-CeO2 / Fe2O3 / FF catalyst in Experimental Example 5, the muffle furnace calcination temperature was set to uncalcined, 200°C, 300°C, 400°C and 500°C, respectively, and the tetracycline concentration was measured by sampling at 75 minutes of reaction, and the remaining steps were the same as Experimental Example 1. The effect of calcination temperature in the process from solid 3 to solid 4 on the removal efficiency of tetracycline by the prepared CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined through experiments.
[0068] Experimental Example 6
[0069] Different from Experimental Example 1, in the process of forming solid 4 from solid 3 when preparing the CuO-CeO2 / Fe2O3 / FF catalyst in Experimental Example 6, the muffle furnace calcination time was set to 0min, 30min, 60min and 120min respectively, and the tetracycline concentration was measured by sampling at 75min of the reaction. The remaining steps were the same as those in Experimental Example 1. The effect of the calcination time in the process of solid 3 to solid 4 on the removal efficiency of tetracycline by the prepared CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0070] Experimental Example 7
[0071] Different from Experimental Example 1, the current density of the power source in Experimental Example 7 is 1 mA / cm 2 , 3mA / cm 2 , 6mA / cm 2 , 9mA / cm 2 , 12mA / cm 2 and 15mA / cm 2 , and the rest of the steps are the same as those in Experimental Example 1. The effect of current density on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0072] Experimental Example 8
[0073] Different from Experimental Example 1, the aeration rates in Experimental Example 8 were 0 L / min, 0.1 L / min, 0.3 L / min, 0.6 L / min and 0.9 L / min, respectively, and the remaining steps were the same as those in Experimental Example 1. The effect of aeration rate on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0074] Experimental Example 9
[0075] Different from Experimental Example 1, the pH of the reaction solution in Experimental Example 9 was adjusted to 3.0, 5.0, 7.2 and 9.0 respectively, and the remaining steps were the same as those in Experimental Example 1. The effect of solution pH on the efficiency of removing tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0076] Experimental Example 10
[0077] Different from Experimental Example 1, the electrolyte solutions in Experimental Example 10 were replaced with 0.05 mol / L NaCl, 0.05 mol / L NaNO3, and 0.05 mol / L Na2SO4, respectively, and the remaining steps were the same as those in Experimental Example 1. The effect of electrolyte type on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in the electro-Fenton system was determined through experiments.
[0078] Experimental Example 11
[0079] Different from Experimental Example 1, the initial concentrations of tetracycline in Experimental Example 11 were set to 2.5 mg / L, 5 mg / L, 10 mg / L, 15 mg / L, and 20 mg / L, respectively, and the remaining steps were the same as those in Experimental Example 1. The effect of the initial concentration of tetracycline on the efficiency of removing tetracycline by the CuO-CeO2 / Fe2O3 / FF catalyst in the electro-Fenton system was determined by experiments.
[0080] Experimental Example 12
[0081] Different from Experimental Example 1, in Experimental Example 12, tap water, ultrapure water, pure water, lake water, and river water were used to prepare a 0.05 mol / L Na2SO4 solution, and the remaining steps were the same as those in Experimental Example 1. The effect of the drinking water matrix type on the efficiency of the CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in the electro-Fenton system was determined through experiments.
[0082] Experimental Example 13
[0083] Different from Experimental Example 1, in Experimental Example 13, the catalyst was rinsed with deionized water and dried after the reaction in Experimental Example 1, and the dried catalyst was reused. The other experimental parameters and steps were the same as those in Experimental Example 1. This operation was repeated 8 times, and the reusability of the prepared CuO-CeO2 / Fe2O3 / FF catalyst for removing tetracycline in the electro-Fenton system was determined through the catalyst reuse experiment.
[0084] Experimental Example 14
[0085] Different from Experimental Example 1, the target pollutants in Experimental Example 14 were replaced with ciprofloxacin, sulfasalazine, atrazine, and imidacloprid at the same concentrations as tetracycline in Experimental Example 1, and the remaining steps were the same as Experimental Example 1. The removal efficiency of different types of pollutants in the electro-Fenton system with CuO-CeO2 / Fe2O3 / FF as the catalyst was determined through experiments.
[0086] The experimental results are as follows:
[0087] Figure 8 The efficiency of removing tetracycline from drinking water by CuO-CeO2 / Fe2O3 / FF catalyst in heterogeneous electro-Fenton system under optimal conditions. The results of Experimental Example 1 show that the CuO-CeO2 / Fe2O3 / FF catalyst can efficiently remove tetracycline from drinking water in heterogeneous electro-Fenton system, and the tetracycline removal rate can reach 100% at 75 minutes of reaction.
[0088] Fig. 9The effect of metal ratio on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in heterogeneous electro-Fenton system. The results of Experimental Example 2 show that different ratios of Cu and Ce will affect the efficiency of the prepared catalyst in removing tetracycline from drinking water in heterogeneous electro-Fenton. By comparing the tetracycline removal efficiency at different ratios, the optimal molar ratio of Cu to Ce is 3:1.
[0089] Fig.10 The effect of hydrothermal temperature on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in a heterogeneous electro-Fenton system. The results of Experimental Example 3 show that a hydrothermal temperature of 120°C can form a stable structure of the catalyst and efficiently remove tetracycline from drinking water in a heterogeneous electro-Fenton system. Too high or too low a temperature will affect its catalytic activity.
[0090] Fig.11 The effect of hydrothermal time on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in a heterogeneous electro-Fenton system. The results of Experimental Example 4 show that a hydrothermal time of 12 hours can form a stable structure of the catalyst and efficiently remove tetracycline from drinking water in a heterogeneous electro-Fenton system. A hydrothermal time that is too long or too short will affect its catalytic activity.
[0091] Fig.12 The effect of calcination temperature on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in a heterogeneous electro-Fenton system is shown in Experiment 5. The results of Experiment 5 show that a calcination temperature of 400°C can make the catalyst structure more stable and reduce the shedding of the supported metal. A calcination temperature that is too high will destroy the stability of the structure, and a temperature that is too low will easily cause the metal to fall off, thus affecting its catalytic ability.
[0092] Fig.13 The effect of calcination time on the efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline from drinking water in a heterogeneous electro-Fenton system is shown in Experimental Example 6. The results of Experimental Example 6 show that a calcination time of 60 minutes can make the catalyst structure more stable and reduce the shedding of the loaded metal. A calcination time that is too long will destroy the structural stability of the material, and a calcination time that is too short will easily cause the loaded metal to fall off, thus affecting its catalytic ability.
[0093] Fig.14 The effect of current density on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system is shown in Experimental Example 7. The results of Experimental Example 7 show that the removal efficiency of tetracycline increases with the increase of current density. When the current density is 0.09A and 0.12A, the tetracycline removal rate at 75min of reaction is 100%. Considering the operating cost of the process, 0.09A is preferably selected as the optimal current density.
[0094] Fig.15 The effect of aeration rate on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in a heterogeneous electro-Fenton system is shown in the figure. The results of Experimental Example 8 show that the higher the aeration rate, the higher the removal efficiency of tetracycline in the system. When the aeration rate is 0.6L / min and 0.9L / min, the tetracycline removal rate at 75min of reaction is 100%. Considering the operating cost of the process, 0.6L / min is preferably selected as the optimal aeration rate.
[0095] Fig.16 The effect of solution pH on the efficiency of tetracycline removal by CuO-CeO2 / Fe2O3 / FF catalyst in heterogeneous electro-Fenton system. The results of Experimental Example 9 show that when the solution pH is less than 7.2, the tetracycline removal rate at 75 min of reaction is 100%, and when the solution is weakly alkaline (pH = 9.0), the tetracycline removal rate can still reach a high removal rate of 91%, indicating that the prepared catalyst has extremely strong stability in the heterogeneous electro-Fenton system, which well overcomes the problem of narrow applicable pH range of traditional Fenton and electro-Fenton systems.
[0096] Fig.17 The effect of electrolyte type on the removal efficiency of tetracycline by CuO-CeO2 / Fe2O3 / FF catalyst in heterogeneous electro-Fenton system. The results of Experimental Example 10 show that Na2SO4 and NaCl have little effect on the removal of tetracycline by the catalyst in the heterogeneous electro-Fenton system, and the removal rate of tetracycline is more than 90%, indicating that the prepared catalyst has good applicability. When NaNO3 is used as the electrolyte of the system, the NO3 - This affects the solution conductivity, thereby reducing the current efficiency of the system and the reaction rate of the target product.
[0097] Fig.18 The effect of the initial concentration of tetracycline on the removal efficiency of tetracycline in the heterogeneous electro-Fenton system of CuO-CeO2 / Fe2O3 / FF catalyst is shown in the results of Experimental Example 11. The removal rate gradually decreases with the increase of the initial concentration of tetracycline, but it still maintains a high removal rate level. When the initial concentration of tetracycline is 20 mg / L, the removal rate reaches 82% after 75 minutes of reaction; when the initial concentration of tetracycline is below 10 mg / L, the removal rate reaches 100% after 75 minutes of reaction.
[0098] Fig.19The effect of drinking water matrix type on the tetracycline removal efficiency of CuO-CeO2 / Fe2O3 / FF catalyst in the heterogeneous electro-Fenton system. The results of Experimental Example 12 show that when CuO-CeO2 / Fe2O3 / FF is used as a catalyst, the efficiency of removing tetracycline from drinking water by the heterogeneous electro-Fenton system will be affected to a certain extent by the drinking water matrix, but it can still maintain a high tetracycline removal rate. Among them, for lake water, the tetracycline removal rate is 82% after 75 minutes of reaction; for municipal tap water, the tetracycline removal rate is 89% after 75 minutes of reaction; for river water, the tetracycline removal rate is 92% after 75 minutes of reaction. It can be seen that the prepared catalyst is less affected by the actual drinking water matrix, and the prepared catalyst has good engineering application potential.
[0099] Fig. 20 The removal efficiency of tetracycline in drinking water when the CuO-CeO2 / Fe2O3 / FF catalyst is recycled and reused 8 times in a heterogeneous electro-Fenton system. The results of Experimental Example 13 show that the efficiency of the CuO-CeO2 / Fe2O3 / FF catalyst in removing tetracycline in a heterogeneous electro-Fenton system still reaches a high efficiency of 86% when the catalyst is recycled 8 times (the total use time reaches 600 minutes). It can be seen that the prepared catalyst has extremely high stability in application, and it can be put into use again after only rinsing it with deionized water before reuse, which has extremely high engineering application potential and significantly reduces the regeneration cost of the catalyst.
[0100] Fig.21 The removal efficiency of different types of target pollutants in the heterogeneous electro-Fenton system with CuO-CeO2 / Fe2O3 / FF as the catalyst. The results of Experimental Example 14 show that the CuO-CeO2 / Fe2O3 / FF catalyst has a good removal effect on ciprofloxacin, tetracycline, sulfasalazine, atrazine, and imidacloprid, that is, the system has good applicability for the removal of different types of pollutants.
[0101] The above experimental results show that the present invention loads copper-cerium layered double hydroxide CuCe-LDH on the FF substrate grown with Fe-MOF / FF to make its structure more stable, and constructs a composite material CuO-CeO2 / Fe2O3 / FF with a high specific surface area and porous structure. This design not only enhances the physical adsorption capacity and catalytic activity of the catalyst, but also improves the stability of the catalyst and facilitates recycling.
[0102] The present invention ensures the close combination of CuCe-LDH and Fe-MOF / FF by optimizing the hydrothermal reaction conditions (such as hydrothermal temperature, time, etc.), calcination temperature and calcination time, realizes the structural stability and high catalytic performance of the composite material, and enables it to maintain high catalytic activity and pollutant removal efficiency after multiple reuses or long-term reaction.
[0103] The catalyst is suitable for removing different types of new organic pollutants in drinking water, and can effectively remove a variety of antibiotic pollutants, especially tetracycline, in a short treatment time. By optimizing and adjusting the reaction conditions (such as current density, aeration volume, solution pH, etc.), the removal efficiency of the target substances in drinking water can be further improved, ensuring the high efficiency and stability of the catalyst in practical engineering applications.
[0104] The embodiments described above are merely descriptions of preferred implementation modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water, characterized in that: First, the foamed iron is soaked in dilute hydrochloric acid and ultrasonically treated, then soaked in ethanol and ultrasonically treated, and then rinsed with deionized water to obtain a solid 1; terephthalic acid is dissolved in deionized water to obtain a solution 1; The solution 1 is transferred to a reactor, and the solid 1 is placed in the reactor for hydrothermal reaction; when the reaction is completed and cooled to room temperature, the obtained solid is repeatedly washed with deionized water, and then placed in a drying oven at a constant temperature of 80°C to dry to obtain a solid 2, which is named Fe-MOF / FF; Solution 2 was prepared at room temperature by dissolving weighed Ce(NO3)3·6H2O, Cu(NO3)2·3H2O, ammonium fluoride and urea in deionized water, and then adjusting the pH to a neutral range using a mixed solution of Na2CO3 and NaOH. Solution 2 was then transferred to a reactor, and solid 2 was placed on the inner wall of the reactor. The reactor was placed in a drying oven and heated at a constant temperature, and then the obtained solid was washed and dried to obtain solid 3, named CuCe-LDH / Fe-MOF / FF. Finally, the solid three is placed in a muffle furnace and calcined to obtain the solid four, which is the CuO-CeO2 / Fe2O3 / FF catalyst.
2. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The specific preparation method of the solid one is to soak a 2cm×2cm foam iron in 3mol / L dilute hydrochloric acid for ultrasonic treatment for 30 minutes, then soak it in ethanol for ultrasonic treatment for 30 minutes, and finally rinse it with deionized water to obtain the solid one.
3. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The specific preparation method of the solution one is as follows: 2 mmol of terephthalic acid is added into 60 mL of deionized water, and the mixture is continuously stirred until the terephthalic acid is completely dissolved, thereby obtaining the solution one.
4. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The specific preparation method of the solid two is to transfer the solution one to a reactor with a volume of 100 mL and a polytetrafluoroethylene lining, place the solid one in the reactor, and react at 150° C. for 12 hours; after the reaction is completed, cool it to room temperature, wash it repeatedly with ethanol and deionized water in turn, and then dry it at 80° C. to obtain the solid two, named Fe-MOF / FF.
5. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The specific preparation method of the solution 2 is as follows: 4 mmol of Ce(NO3)3·6H2O, 12 mmol of Cu(NO3)2·3H2O, 20 mmol of ammonium fluoride and 80 mmol of urea are dissolved in 20 mL of deionized water and mixed evenly with ice, and the pH value is adjusted to 7.4-7.5 using a mixed solution of Na2CO3 and NaOH to obtain solution 2; wherein the concentration of the Na2CO3 is 0.6 mol / L, and the concentration of the NaOH is 0.3 mol / L.
6. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The molar ratio of Cu:Ce in the second solution is 3:
1.
7. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The total molar number of Cu and Ce in the second solution is controlled at 16 mmol.
8. The method for preparing a solid catalyst for treating residual antibiotics or pesticides in drinking water according to claim 1, characterized in that: The specific preparation method of the solid three is as follows: after transferring the solution two into a polytetrafluoroethylene-lined reactor, the solid two is placed on the inner wall of the reactor; the reactor is placed in a forced air drying oven, heated at a constant temperature of 120° C. for 12 hours, and then the obtained solid is repeatedly washed with ethanol and deionized water in sequence, and dried in an oven at 80° C. to obtain the solid three; The specific preparation method of the solid four is to place the solid three in a muffle furnace and calcine at 400° C. for 1 hour to obtain solid four.
9. The solid catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the solid catalyst according to claim 9 in treating residual antibiotics or pesticides in drinking water, characterized in that: The antibiotics include tetracycline, ciprofloxacin and sulfasalazine, and the pesticides include atrazine and imidacloprid; The solid catalyst is used to treat residual antibiotics or pesticides in drinking water through a heterogeneous electro-Fenton reaction, and the current density of the electro-Fenton reaction is 9 mA / cm 2 , aeration volume was 0.6L / min, and pH value was 7.2.
Citation Information
Patent Citations
Two dimensional catalytic material derived from metal-organic frameworks and application thereof in removal of volatile organic compounds (VOCs)
CN110787788A
Preparation method and application of Fe-Ce-LDH / 13X granular catalyst for heterogeneous electro-Fenton system
CN113842942A
Preparation method of FeVO4-FeCeO3 nanoparticle doped ceramic membrane catalytic reactor
CN117619397A